PENERAPAN KONSEP PEMBELAJARAN AKTIF, KREATIF, EFEKTIF, DAN MENYENANGKAN (PAKEM) DALAM MENYIMAK PUISI UNTUK MENINGKATKAN KEMAMPUAN APRESIASI SASTRA - Isnaeni Praptanti; Karma Iswasta Eka (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2010)
This research aimed to improve the students’ ability of literature through PAKEM concept in teaching learning process using picture cards to the students of PGSD S1 academic year 2010-2011. The research was the class action research with the research subject of all students of The Elementary School Teacher Education S1 academic year 2010-2011 class D, which consisted of 51 students, 16 male students, and 35 female students. The research process was done in two cycles; each cycle consisted of 2 meetings. Each meeting consisted of 2 lecture-hours (2x50 minutes). To know the first condition, it was conducted the pre-test, and the data of pre-test was used as the basic action of the fist cycle. After delivering the material of poem by applying the concept of PAKEM using the media of picture cards, it was continued by the post-test of the first cycle. The data of post- test I was used as the action of the second cycle, and it was ended by the analysis and the reflection of all cycles. The data collection was done by using test and non-test. Using test was by pre-test and post-test, and non-test was by observation, interview and documentation. The source used to process the data was score or from the quantitative data (the poem- writing score) and qualitative data. The result of the processing data was used to describe the achievement of the action towards the improvement of the students’ literature appreciation through PAKEM concept using the media of picture cards. It could be proven from the result of the research, observation and evaluation. After the action, it was proven that students’ literature appreciation improved in writing poem. In the cycle 1, it was found that 52% of the students were successful and 48% of them were not yet successful with the average point of 72. In the cycle 2, it, it was found that 75% of the students were successful and 20% of them were not yet successful with the average point of 77. Based on this description, it was concluded that the application of PAKEM concept using picture cards could improve the literature appreciation of S1 PGSD students in academic year 2010-2011. Key Words: active, creative, effective, and fun learning concept,listening to poem.